2018
DOI: 10.1186/s13014-018-1123-x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the gamma index analysis as a verification method of volumetric modulated arc therapy plans

Abstract: BackgroundWe investigate the gamma passing rate (GPR) consistency when applying different types of gamma analyses, linacs, and dosimeters for volumetric modulated arc therapy (VMAT).MethodsA total of 240 VMAT plans for various treatment sites, which were generated with Trilogy (140 plans) and TrueBeam STx (100 plans), were retrospectively selected. For each VMAT plan, planar dose distributions were measured with both MapCHECK2 and ArcCHECK dosimeters. During the planar dose distribution measurements, the actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…However, previous studies have mainly focused on the correlation analysis between gamma results and DVH deviations. Similar to our findings, previous studies reported weak or absence of correlation between GFR and DVH deviations in VMAT [17][18][19][20] and IMRT [21][22][23][24] plans for prostate cancers [17,18,20,23], as well as for other cancers [19][20][21][22][23][24]. Fundamentally, clinically relevant DVH parameters are extracted from the statistical analyses for the entire dose distribution, despite gamma results evaluating dose differences point by point.…”
Section: Discussionsupporting
confidence: 82%
“…However, previous studies have mainly focused on the correlation analysis between gamma results and DVH deviations. Similar to our findings, previous studies reported weak or absence of correlation between GFR and DVH deviations in VMAT [17][18][19][20] and IMRT [21][22][23][24] plans for prostate cancers [17,18,20,23], as well as for other cancers [19][20][21][22][23][24]. Fundamentally, clinically relevant DVH parameters are extracted from the statistical analyses for the entire dose distribution, despite gamma results evaluating dose differences point by point.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, gamma index analysis was performed by comparing the raw data of the array measurements to TPS calculated dose distributions using gamma index criteria of 3 mm/3% and 2 mm/2% 37 . The evaluation was differentiated between global gamma index analysis (dose difference is calculated from the maximum dose of the investigated field) and local gamma index analysis (dose difference is calculated from the local dose at the point of evaluation) 38 . All dose values below 10% of the maximum dose were suppressed.…”
Section: Methodsmentioning
confidence: 99%
“…37 The evaluation was differentiated between global gamma index analysis (dose difference is calculated from the maximum dose of the investigated field) and local gamma index analysis (dose difference is calculated from the local dose at the point of evaluation). 38 All dose values below 10% of the maximum dose were suppressed.…”
Section: E3 Intensity Modulated Treatment Plansmentioning
confidence: 98%
“…The evaluation was based on a retrospective setting with a relatively large sample size ( n = 344), and all treatment plans and QA data were generated from the same TPS and delivered by the same Linac with the same 2D detector array in our department. Previous reports showed that GPR for the same plan varied with the types of dosimeters and QA software [40, 41]. Although not in true 3D with high spatial resolution, dose distributions measured with nonplanar detector arrays can give a more realistic picture of VMAT delivery compared with planar dose distributions using 2D arrays [4244].…”
Section: Discussionmentioning
confidence: 99%